Distrofija pri otroku in pomen pravilne prehrane - Šmid, Erika (Slovenska pediatrija, 2010)
This paper describes the case of a 2.5-year-old child with failure to thrive in whom coeliac disease was diagnosed during his hospital stay. Coeliac disease and its major characteristics are described as well as the effects of proper diet on the patient's clinical state. The diagnostic workup and the role of the nursing sister in dealing with a child with coeliac disease are described.
Keywords: Celiac Disease; Celiakija; Child, Preschool; Diet Therapy; distrofija; Gluten; Growth Disorders; Nursing; otroci; Otrok predšolski; prehrana; Rast, motnje